CFD analysis of Fe transfer on roughened wall caused by turbulent lead-bismuth eutectic flow - Chen, Xiaolin; Wan, Tao (Frontiers in Energy Research, 2022)
Structural material compatibility with lead bismuth eutectic is one of the main challenges for design and operation of the LBE-cooled nuclear systems. To better understand the mechanisms of stainless steel corrosion behavior in LBE flow, the iron mass transfer phenomenon on roughened walls under various LBE pipe flow conditions are numerically investigated in this study. CFD simulations are performed, by applying a low Reynolds number k-ε model, in a range of Reynolds number from 5 × 103 to 105. Meanwhile, various pipe wall roughness conditions are considered, which are simulated by crests with different depths and periodic lengths. Effects of roughness dimensions and Reynolds numbers on the near-wall mass transfer rate are investigated. Results showed that higher flow velocities and shorter crest length led to higher mass transfer coefficient. On the basis of the results, the mass transfer coefficients are proposed both for smooth wall and roughened walls. The mass transfer enhanced by wall roughness is characterized by the ratio of rough-to-smooth mass transfer coefficient, and this ratio is demonstrated by a regression equation, in which dimensionless roughness number, Reynolds number and geometrical ratio of the roughness are included. Moreover, it is found that the ratio of rough-to-smooth mass transfer coefficient is relatively more dependent on Reynolds number.